2011
DOI: 10.1111/j.2041-1626.2010.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion and storage media

Abstract: Avulsion of a tooth caused by trauma, and its successful treatment is a challenging situation that a dentist encounters in clinical practice. There is a definitive treatment for the avulsed tooth, which depends on many factors. The immediate replacement and replantation of the avulsed tooth is necessary, but it cannot always be accomplished for a number of reasons. Thus, the tooth should be transported in a suitable medium to maintain the cell viability. The storage medium is one of the important factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…If immediate replantation is not possible, PDL cell damage should be avoided by placing the tooth in an appropriate storage medium, such as milk or saliva. The majority of the videos suggested an appropriate medium, and 31% (n = 5) suggested water as a storage solution, which has been shown to reduce prognosis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If immediate replantation is not possible, PDL cell damage should be avoided by placing the tooth in an appropriate storage medium, such as milk or saliva. The majority of the videos suggested an appropriate medium, and 31% (n = 5) suggested water as a storage solution, which has been shown to reduce prognosis …”
Section: Discussionmentioning
confidence: 99%
“…As these videos are not subjected to any formal peer‐review, there is concern regarding the reliability, degree of accuracy and scientific validity of their content so transmission of ambiguous, erroneous and potentially misleading information could result. Previous studies have demonstrated an inadequate level of public knowledge and awareness with regard to prevention and management of dental trauma, thus highlighting an area where further improvement is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognosis of a replanted tooth will depend on minimal damage to the PDL, which is critical for regeneration of the attachment apparatus and also to protect root from resorption. [1011]…”
Section: Discussionmentioning
confidence: 99%
“…Research quality is what JICD is striving for and in the current issue we have an offering of a number of quality articles from countries such as Syria, Greece, Thailand, India and Hong Kong on issues that range from psychological disorders and oral problems, 3 craniofacial parameters of Syrian children with β‐thalassemia, 4 and a review on how best to store avulsed teeth 5 …”
mentioning
confidence: 99%